Assessing Awareness and Opinions on Anti-Corruption and Integrity Education in Malaysian Secondary School - Mohd Badri, Muhammad Hazim; Mohd Razali, Siti Noor Asyikin (Enhanced Knowledge in Sciences and Technology, 2026)
This study investigates secondary school students’ awareness of anti-corruption and their views on anti-corruption and integrity education in Malaysia. Data were collected from 278 students using a structured questionnaire with Likert-scale items measuring awareness, perceived effects, challenges, and solutions related to anti-corruption education. Descriptive statistics were used to analyse demographic characteristics and were visualised through an interactive Power BI dashboard. As the data were not normally distributed, the Mann–Whitney U test and Kruskal–Wallis H test was employed. The results indicate a statistically significant difference in anti-corruption awareness based on participation in school integrity programmes; however, contrary to expectations, students who did not participate reported higher levels of awareness, with the relationship exhibiting a small effect size. No statistically significant differences, with negligible practical effects, were observed across gender, race, year of study, or participation in anti-corruption awareness programmes in relation to awareness. In contrast, students’ opinions on the effects, challenges, and solutions of anti-corruption education differed significantly by gender, participation in school integrity programmes, and year of study, although these relationships were characterised by small effect sizes. Overall, the findings suggest that while certain demographic and programme-related factors are statistically relevant, their practical influence remains limited, underscoring the need to reassess the effectiveness of integrity education at the secondary school level.